2009
DOI: 10.1603/033.046.0412
|View full text |Cite
|
Sign up to set email alerts
|

Control of Phlebotomine Sand Flies With Vertical Fine-Mesh Nets

Abstract: Insecticide-treated vertical net barriers were used to intercept foraging sand flies. Two different nets were draped on fenced enclosures (10 by 10 m; 2 m high) in the central Jordan Valley. One enclosure was draped with a deltamethrin-impregnated net (PermaNet, 225 holes/in2). The holes of this net are sufficiently large to allow sand flies to pass through but not without coming in close contact with the mesh. The other enclosure was covered with SpiderNet+ (1,240 holes/in2) and sprayed with beta-cyfluthrin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Sustainable livestock and dairy production systems should be economically viable, environmentally sound and socially responsible. While resistance continues to be an issue, ITN has been used with great success in livestock systems, and careful choice of insecticide formulation, rotation among insecticide classes and minimization of the ITN deployment interval are sure to be central goals of a comprehensive resistance management program. Adoption of ITN technology, with its low cost and durability, precise application method and widening societal acceptance, may be one step towards sustainable livestock production systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable livestock and dairy production systems should be economically viable, environmentally sound and socially responsible. While resistance continues to be an issue, ITN has been used with great success in livestock systems, and careful choice of insecticide formulation, rotation among insecticide classes and minimization of the ITN deployment interval are sure to be central goals of a comprehensive resistance management program. Adoption of ITN technology, with its low cost and durability, precise application method and widening societal acceptance, may be one step towards sustainable livestock production systems.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large pyrethroid‐treated ITN literature for biting flies, with recent papers focused on mosquitoes . Pyrethroid‐treated netting has been evaluated for use in outdoor livestock containment facilities for control of tsetse flies ( Glossina spp., Diptera: Glossinidae) and biting midges ( Culicoides spp., Diptera: Ceratopogonidae) and as a peridomestic barrier for the control of phlebotomine sand flies (Diptera: Psychodidae) . Although the authors could find no research on the use of ITN to control face flies, in a recent study in Ghana, the impact of deltamethrin‐treated nets for the control of flies from the subfamilies Muscinae (but not face fly) and Stomoxyinae and the family Tabanidae attacking cattle in pens was evaluated …”
Section: Introductionmentioning
confidence: 99%
“…Several attempts to apply the LLITNs to the other vectors, such as Ae. aegypti (Curtis et al, 1996;Igarashi, 1997;Kroeger et al, 2006;Jeyalakshmi et al, 2006) and Phlebotomus (Dinesh et al, 2008;Faiman et al, 2009;Emani et al, 2009;Kasili et al, 2010;Das et al, 2010), have been performed and trials to apply the LLITNs as the other controlling tools, such as curtains (Curtis et al, 1996;Igarashi, 1997;Kroeger et al, 2006;Vanlerberghe et al, 2011a; and jar covers (Kroeger et al, 2006;Vanlerberghe et al, 2011a;, have been reported using Olyset ® Net and/or PermaNet ® . In this section, a new attempt for controlling Ae.…”
Section: Preventive Effect Of Release Controlled Plastic Net Of Permementioning
confidence: 99%
“…To test this hypothesis, a 60 m‐long insecticide‐impregnated fine‐mesh polyester barrier was erected between a natural habitat from where sand flies were approaching and a row of houses on the outskirts of a desert town in Israel. The mesh barrier proved partially efficient (60% reduction) at blocking sand flies (mainly P. sergenti ) approaching houses (Faiman et al 2009). In later studies conducted in a different location in Israel, a longer barrier (400 m) was proven far more effective (85% reduction, P. papatasi) (Faiman and Warburg, unpublished data).…”
Section: Introductionmentioning
confidence: 99%